LEGAL PROTECTION OF PERSONAL DATA IN THE FUNCTION OF PROTECTION OF HUMAN RIGHTS AND FREEDOMS - Krasniqi, Safet (International Journal of Research -GRANTHAALAYAH, 2020)
The era of globalization and digitalization have become a necessary process for the legal and legal regulation of human rights. This is taken into account by the fact that technological-technological advances have increased fears of human rights violations. This is especially noteworthy in communication tools, the internet and so on. With the intent, protection of personal data and privacy In the international sphere, the EU has made the coding of the protection of personal data through Directive no. 95/96 EC, which entered into force on 24 October 1995, then the ECHR, the European Commission proposal, January 2012, on the reform of the European Data Protection Regulations, which was formulated in the Regulation which came into force on 24 May, 2016 and the General Directive, which entered into force on May 5, 2016. However, according to surveys made with EU citizens, credibility for the protection of personal data from EU institutions and those of member states is below the minimum. The protection of privacy in Kosovo is being done through the legislation and the establishment of the State Agency for the Protection of Personal Data even though Kosovo does not have sufficient technical and material resources for the minimal protection of personal data and privacy in general. This topic addresses the issue of providing information, the confidentiality of the data subject and the security of proceedings and the supervisory authority. Also, the instructions contained in the regulations, the sanctioning of these rights under the penal code necessarily make the approval of the telecommunications law in Kosovo.